Reframing consciousness - Ascott, Roy (Intellect, 1999)
We are in the middle of a process of complex cultural transformation, but to what extent is this matched by the transformation in the way we see ourselves? This book covers a wide-ranging discussion on the interaction between Art, Science and Technology, and goes on to challenge assumptions about 'reality'. Loosely themed around four key elements of Mind, Body, Art and Values, the editor leads the investigation through the familiar territories of interactive media and artificial life, combining them with new and ancient ideas about creativity and personal identity. The contributing authors numb.